Memórias e experiências da educação do campo ao nível superior - Faustino, Antonia Cristina da Silva (Brasil, 2024)
This descriptive work aims to narrate the reflections from when I was a child, to my adult life in rural education, to the present day as a pedagogy undergraduate student. The objective of this work is to clarify how this academic process began in the riverside school in the Amazon region. I believe that a closer look at education in the countryside is necessary. Through my personal life story, with the opportunity to attend a pedagogy college via a teacher training program for those who did not have undergraduate training, it is possible to see that various transformations and reflections were promoted, which, according to my readings, 1 realized on a personal level, and are reflected on other levels as well. My trajectory and experiences during my years of schooling in elementary and secondary education, as well as my career as a teacher in rural and urban areas and all the experiences kept in my memory during my academic training period, in the PARFOR Pedagogy course offered by the Federal University of Amazonas-UFAM.